2013
DOI: 10.1371/journal.pone.0059402
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Affects Bone Resorption and Suppresses the Expression of Cathepsin K, MMP-9 and Vacuolar-Type H+-ATPase d2 and Actin Organization in Osteoclasts

Abstract: Tobacco smoking is an important risk factor for the development of several cancers, osteoporosis, and inflammatory diseases such as periodontitis. Nicotine is one of the major components of tobacco. In previous study, we showed that nicotine inhibits mineralized nodule formation by osteoblasts, and the culture medium from osteoblasts containing nicotine and lipopolysaccharide increases osteoclast differentiation. However, the direct effect of nicotine on the differentiation and function of osteoclasts is poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 50 publications
2
51
0
4
Order By: Relevance
“…In another study, Henemyre et al (), exposed porcine mature osteoclasts to nicotine (0.03–1.50 μg/ml) and found that the number of osteoclasts increased in a linear relationship with the increase on nicotine concentration, although they did not find any correlation between osteoclast number and the amount of resorption observed (Henemyre et al, ). Recently, Tanaka et al () reported that nicotine caused a negative effect in osteoclast resorbing ability in RAW264.7 murine cell line treated with RANKL, for concentrations ≥16 μg/ml (Tanaka et al, ). Although with evident differences in the experimental protocols, these studies suggest that nicotine, in the microgram range, seems to cause negative effects on osteoclastic behavior, as it was observed in the present work with human cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Henemyre et al (), exposed porcine mature osteoclasts to nicotine (0.03–1.50 μg/ml) and found that the number of osteoclasts increased in a linear relationship with the increase on nicotine concentration, although they did not find any correlation between osteoclast number and the amount of resorption observed (Henemyre et al, ). Recently, Tanaka et al () reported that nicotine caused a negative effect in osteoclast resorbing ability in RAW264.7 murine cell line treated with RANKL, for concentrations ≥16 μg/ml (Tanaka et al, ). Although with evident differences in the experimental protocols, these studies suggest that nicotine, in the microgram range, seems to cause negative effects on osteoclastic behavior, as it was observed in the present work with human cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that co‐cultures of mouse bone marrow and ST2 cells displayed an inhibition of osteoclastogenesis caused by nicotine (Yuhara et al, ). In another study, nicotine stimulated the resorbing activity of porcine osteoclastic cells (Henemyre et al, ), whereas, in a more recent work, nicotine reduced the resorbing ability of RAW264.7 murine cells (Tanaka et al, ). The different protocols and the origin of the analyzed cells might explain the apparent observed contradictions, and reinforces the need to address this issue in more detail and in a more representative model, as in human primary osteoclastic cells.…”
Section: Introductionmentioning
confidence: 95%
“…The two latter factors were marked in the present study: smoking was more common in obese subjects, and HEI, mirroring dietary quality, was lower than in normal-weight controls. Smoking may affect bone turnover through several mechanisms [36,37]. Interestingly, in subjects with severe early-onset obesity, smoking associated positively with bone size and with polar SSI both in proximal radius and diaphyseal tibia.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, some other controversial conclusions regarding the effect of nicotine on bone cells have been reported. Tanaka et al 9 found that nicotine induces osteoclasts with the small number of nuclei, but reduces the number of osteoclasts with many nuclei at the same time. Some investigations on the influence of nicotine on the proliferation of osteoblasts came to the adverse conclusion that one study reported that nicotine decreases cell proliferation in rat osteoblastic osteosarcoma cells, 20 while another suggested the stimulation effect of nicotine in murine clonal osteoblast-like osteogenic MC3T3-E1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies reported that nicotine stimulated the formation and differentiation of osteoclasts, 7,8 suppressed osteogenesis in osteoblasts, directly stimulated osteoclast precursors, and induced an imbalance of osteoblasts and osteoclasts in vitro. 9, 10 Rothem et al 11 suggested that nicotine affected osteoblast cell proliferation in a biphasic manner, including toxic and antiproliferative effects at high levels of nicotine and stimulatory effects at low levels. 11 In a word, the cellular effects of nicotine are still controversial.…”
Section: Introductionmentioning
confidence: 99%